Oil palm trunk plywood production using copolymerized and modified phenolic resins - Yeoh, Beng Hoong (2014)
Nowadays, the use of waste material such as, saw dust, rice husk, coconut coir, empty fruit brunch (EFB), oil palm mass and oil palm stem (OPT) as alternative material for wood-based industry in producing various commercial product have been extensively explored. Nevertheless, the used of OPT as raw material replacing hardwood species in plywood production has been in practice for the past 10 years. However, high resin consumption and low mechanical properties in OPT plywood are still the limitation. Hence, in this study we explored the potential of a new resin treatment approach using LmwPF in order to produce high grade OPT plywood. In this work, the effects of several factors such as properties such as, thickness swelling, water absorption, hot-press pressure, bonding integrity, density, the modulus of rupture (MOR) and modulus of elasticity (MOE). The LmwPF resin treatment of OPT in plywood production indicated that with this new resin treatment method (1st part of pilot scare study), improvement of > 200% in strength, > 259% in stiffness, dimensional stability (> 6% thickness swelling and > 36% water absorption) as well as, 28% and 80% greater in dry and WBP shear under hot-pressing pressure at 20 bar at the first 5 min and increased to 50 bar for the next 9 min, respectively as compare to the conventional method of commercial OPT plywood. While the 2nd part of pilot scale study showed that, the mechanical properties and bonding performance of the pre-preg OPT plywood were influenced by the different pressing time (14, 16, 18 and 20 min). The high grade OPT plywood with improved at least 227 % MOR and 348 % MOE compared to commercial OPT plywood, with greater in MOR (31 %) and MOE (12 %) higher compared than the commercial tropical mix light hardwood (MLHW) plywood at 20 min hot-pressing time with most optimum hot-pressing pressure obtained from previous study. Moreover, the performance of the formaldehyde emission, some mechanical properties and bonding quality of oil palm trunk (OPT) plywood treated with low molecular weight phenol-formaldehyde (LmwPF), as affected by resin concentration. The mechanical properties are affected by different of amount resin contain used. The OPT veneer were treated at either 40 %, 32 %, 23 % or 15 % of resin concentration and 12 mm thickness of 3-ply plywood panel were manufactured for each group. In this study the formaldehyde emission, modulus of rupture (MOR), modulus of elasticity (MOE) and bonding quality (shear strength) of OPT plywood were determined. The results revealed that the resin-treatment method tended to significantly improved the mechanical properties of the OPT plywood panel in which increased solid absorption gives better mechanical properties. Apparently, high mechanical properties were obtained for panel manufacturer from veneer treated with 32 % and 40 % resin content. However, mechanical properties of the resin-treated OPT plywood were drastically decreased with increasing the water substitution. Formaldehyde emission content of OPT panels decreased upon reduction of resin content into treatment process and were significant at resin concentration. The resin-treated OPT panels at 32 % solid content provided a reasonable amount of free formaldehyde (0.359 mg/l) which attained F**** according to Japanese Agriculture Standard (JAS). The matrix-assisted laser desorption/ionisation time of flight (MALDI-TOF) mass spectrometry (MS) and 13C nuclear magnetic resonance (NMR) spectroscopic technique were used to characterize synthesis Phenol-Urea-Formaldehyde (PUF) resin. The MALDI-TOF-MS illustrated and confirmed a series number of the phenol-urea co-condensates repeating unit exit in the prepared PUF resins which corroborated well with the mechanical properties (Modulus of Elasticity and Modulus of Rupture), bonding quality (Dry test and WBP) and physical performance test results. A series of PF, UF and PUF resins oligomers forms repeating unit up to 1833 Da were identified. Besides that, the Solid Stated 13C NMR interpretation indentified that the signal at 44-45 ppm and 54-55 ppm corresponding to methylene bridges was co-condensed in between phenol to urea in the PUF resin system. The 13C NMR investigation showed that the synthesis process of PUF resin had no free formaldehyde elements. In addition, the proportion of urea and methylolureas in the mixture to synthesis PUF resin are sufficient and well corporated into the formulation by reacting with LmwPF units to form co-condensed methylene bridges. The output of this pilot scale study proved that high performance OPT plywood could produced through pre-treatment method in the current plywood mills in which provides broader area of applications compared with conventional OPT plywood. For instant, the pre-preg OPT plywood which is suitable for structural application, concrete formwork, heavy duty interior structuring board, load bearing plywood, marine grade plywood, was obtained, thus consequently increases the price of OPT plywood panels.